2008
DOI: 10.1128/iai.00980-07
|View full text |Cite
|
Sign up to set email alerts
|

A Carcinoembryonic Antigen-Related Cell Adhesion Molecule 1 Homologue Plays a Pivotal Role in Nontypeable Haemophilus influenzae Colonization of the Chinchilla Nasopharynx via the Outer Membrane Protein P5-Homologous Adhesin

Abstract: In vitro studies suggest an important role for CEACAM1 (carcinoembryonic antigen-related cell adhesion molecule 1) in infection by multiple gram-negative bacteria. However, in vivo evidence supporting this role is lacking, largely because the bacterial adhesins involved in this host-microbe association do not bind to murine-derived CEACAM1. One of several adhesins expressed by nontypeable Haemophilus influenzae (NTHI), the outer membrane protein P5-homologous adhesin (or P5), is essential for colonization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…Previously, P5 was implicated in the pathogenesis of H. influenzae as an adherence factor for attachment of H. influenzae to host mucosal structures (42)(43)(44)(45)(46). The work presented here describes new functional roles for this abundant outer membrane protein, including limiting the binding of IgM to the bacterial surface and participating in the binding of fH.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previously, P5 was implicated in the pathogenesis of H. influenzae as an adherence factor for attachment of H. influenzae to host mucosal structures (42)(43)(44)(45)(46). The work presented here describes new functional roles for this abundant outer membrane protein, including limiting the binding of IgM to the bacterial surface and participating in the binding of fH.…”
Section: Discussionmentioning
confidence: 94%
“…Bioinformatic identification of putative DsbA substrates revealed a subset with potential roles in complement resistance (35); the outer membrane protein P5 was selected from this list as a candidate because it is ϳ50% identical to Escherichia coli outer membrane protein A (OmpA) (36), a factor previously shown to be important for complement resistance in E. coli (37)(38)(39). NTHi P5, a ␤-barrel protein with eight predicted transmembrane spans, four outer surface loops (40), and a predicted disulfide between C323 and C335, was shown to be required for virulence in a chinchilla ear infection model (41) and has also been implicated in adhesion of H. influenzae to various mucosal surface structures (42)(43)(44)(45)(46). However, a role for P5 in complement resistance has not been previously reported.…”
mentioning
confidence: 99%
“…Moreover, protection against experimental OM afforded by immunization with rsPilA, chimV4, and IHF was consistent with our understanding of the functions of NTHI OMP P5, Tfp, and IHF in bacterial adherence, pathobiology, and biofilm formation. For example, NTHI Tfp engages ICAM-1, and OMP P5 engages both ICAM-1 and CEACAM-1, molecules whose expression levels on respiratory tract epithelial cells are increased in response to respiratory tract viral infection, including adenovirus (33)(34)(35). Moreover, Tfp and OMP P5 are essential for NTHI to adhere to the mucosal surface.…”
Section: Discussionmentioning
confidence: 99%
“…Also, NTHi adherence to A549 alveolar epithelial cells in vitro was shown to be inhibited in a dose-dependent manner with increasing concentrations of anti-ICAM-1 monoclonal antibodies [52]. An in vivo study conducted in chinchillas reported that anti-CEACAM-1 antibody YTH71.3 effectively blocked NTHi attachment to the nasopharynx [108].…”
Section: Inhibiting Specific Bacterial Adhesin-host Receptor Interactmentioning
confidence: 99%